2008
DOI: 10.1007/s00330-008-0985-y
|View full text |Cite
|
Sign up to set email alerts
|

Giant arachnoid granulation in a patient with benign intracranial hypertension

Abstract: We report magnetic resonance (MR), computed tomography (CT) and angiographic imaging of an unusual giant arachnoid granulation in the superior sagittal sinus in a man with headache and vertigo. Intrasinus pressure measurements revealed a significant pressure gradient across the lesion. MR imaging is useful to identify giant arachnoid granulation and dural sinus thrombosis, whereas dural sinus pressure measurement in certain cases of giant arachnoid granulations can be used to evaluate the lesion as the cause o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…5,6 More recently, so-called giant AGs ranging from 1 to 2.4 cm have been reported. 6,11,13,[17][18][19][20] CSF-like attenuation on CT or fluid that parallels all MR images has been a conventional diagnostic criterion for AGs, though isolated exceptions to this general rule have been reported in the literature. Ikushima et al 3 showed that 10% of AGs averaging 5.1 mm in diameter were slightly hyperintense to CSF on FLAIR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 More recently, so-called giant AGs ranging from 1 to 2.4 cm have been reported. 6,11,13,[17][18][19][20] CSF-like attenuation on CT or fluid that parallels all MR images has been a conventional diagnostic criterion for AGs, though isolated exceptions to this general rule have been reported in the literature. Ikushima et al 3 showed that 10% of AGs averaging 5.1 mm in diameter were slightly hyperintense to CSF on FLAIR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because they are usually located within 3 cm of the midline at the entry of the cortical veins into the sagittal sinus [3,4] where there is a weakness of the dura mater, they could be regarded as arachnoid herniations secondary to intracranial CSF pulsation through dural defects into the sinus [15]. However, giant AGs have also been reported distant from the midline particularly in relation with the transverse sinus [5,6,16]. Greitz et al proposed that AGs are the principal site of CSF re-absorption, considering them as Starling resistors in order to prevent cortical venous collapse during variations in intracranial pressure [17].…”
Section: Development Localization and Clinical Findingsmentioning
confidence: 99%
“…Giant PGs are usually asymptomatic and discovered as incidental findings, although they can give rise to otorrhea, rinorrhea or otitis media [5]. The finding of giant PGs has often been associated with pseudotumor cerebri and benign intracranial hypertension syndrome with headache, vertigo and blurred vision associated to papilledema [13].…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…When arachnoid granulations are enlarged, they are termed "giant". Previous reports have found these structures to be sometimes associated with headaches, and in some patients, idiopathic intracranial hypertension (IIH) may occur (1)(2)(3). The pathophysiology of these enlarged structures seen as filling defects on imaging is not clearly defined, although in some cases they are presumed to cause symptoms such as headache via pressure resulting from secondary venous sinus obstruction.…”
Section: Introductionmentioning
confidence: 99%